Developing Enhanced TSO-DSO Information and Data Exchange Based on a Novel Use Case Methodology - Radi, Mohammed; Taylor, Gareth; Cantenot, Jérôme; Lambert, Eric; Suljanovic, Nermin (Frontiers in Energy Research, 2021)
The growing penetration of Renewable Energy Sources (RES) in the electrical power sector has increased the amount of Distributed Generation (DG) units connected at the distribution system level. In this context, new balancing challenges have arisen, creating the need for a novel Use Case methodology to enable an active role at the distribution system level such that Transmission System Operators (TSOs) can coordinate with Distribution System Operators (DSOs) with regard to connected resources for balancing purposes. In this paper, the exploitation of the DSO connected resources for balancing purposes in a market environment is proposed and evaluated via a novel Business Use Case (BUC) methodology based on the categorisation of IEC 62913-1. More specifically, in order to address different balancing market situations, two scenarios are considered with regard to the BUC. The first one represents the data exchange between the TSO, the DSO and the Balancing Service Provider (BSP). The second one, represents an alternative scenario where data are exchanged directly between the TSO and the DSO, where the DSO also take on the role of the BSP. The proposed BUC was also developed in order to validate the required data modelling and exchange mechanisms between DSOs and TSOs in order to exploit DSO connected resources for overall system balancing purposes across different time scales.